Analyzing The Effect of Theory-Based User Interface Design in Mobile Learning Application on PSTI Students’ Extraneous Cognitive Load - Ikeu Herliana; Jaka Septiadi (FKIP - Universitas Riau, 2026)
The limited screen size of mobile devices can increase users’ Extraneous Cognitive Load (ECL), hindering effective Self-Regulated Learning (SRL) in digital environments. This study aims to design a mobile learning application (MLA) interface integrating User Interface Design (UID) principles with SRL theory and to evaluate its impact on learners’ ECL. Adopting DBR, a prototype was developed and evaluated by 144 respondents using an ECL questionnaire and open-ended feedback. Descriptive statistics revealed that the interface successfully minimized cognitive load, with all dimensions categorized as low. The Aesthetic and Minimalist Design dimension recorded the lowest mean score (2.55). However, thematic analysis revealed issues such as reading fatigue from dense text and subtle navigation cues. Consequently, a design iteration was executed to implement micro-learning content chunking, centralize navigation, and enhance visual signaling. The findings highlight that minimizing ECL through strict UID compliance is essential to support SRL. This research contributes an empirical study by integrating UID principles and SRL theory within a DBR approach to systematically reduce extraneous cognitive burdens.